Effects of Water Stress, Nitrogen, Magnesium and their Interactions on Some Growth Characteristics and Essential Oil content of Rosemary (Rosmarinus officinalis L.) (Baghdad Science Journal, 2023)
A factorial experiment was applied with four replicates on rosemary plants (Rosmarinus officinalis L.) grown in pots inside the glasshouse of the Department of Biology, College of Science, Salahaddin University, Erbil, Iraq, during April, 2019 to July, 2020, to determine the effects of soil moisture content ( SM1: 100% and SM2: 60% field capacity), nitrogen fertilizer (N1: 100, N2: 200 and N3: 300kg/hectare), and magnesium fertilizer (Mg1: 0.0, Mg2: 30 and Mg3: 60kg/hectare) and their interactions on some growth characteristics and essential oil content of rosemary plants. Two cuttings were taken from rosemary shoots (on March, 2020 and July, 2020) after 12 and 15 months of planting respectively. Results showed that cutting 1: SM2 decreased plant height, number of branches, Shoot fresh weight (FW), shoot dry weight (DW), leaves DW & stem DW. N3 increased plant height, number of branches, Shoot FW, shoot DW, leaves DW, stems FW & stem DW. Interaction treatment SM1N3Mg3 increased plant height, Shoot FW, shoot DW, leaves DW, stems FW and stem DW, while in cutting 2: SM2 decreased shoot DW, stems FW and stem DW. N3 increased Shoot FW and stem DW. Mg3 increased Root FW, but decreased stems FW. SM1N3Mg1 increased stem DW. In cutting 1+ cutting 2, SM2 decreased accumulative stem DW and biological yield FW. N3 increased accumulative Shoot FW; Accumulative leaves DW, accumulative stem FW, accumulative yield FW and biological yield DW. Mg3 increased biological yield FW, while SM1N3Mg3 treatment increased accumulative shoot DW, accumulative leaves DW, biological yield FW, and biological yield DW. In the second harvest, SM2 and Mg2 decreased rosemary essential oil %, N3 and SM1N3Mg2increased EO% and concrete content, while SM1Mg2 increased EO.